The antiquities trade in Egypt 1880-1930 : the H.O. Lange papers - Hagen, Fredrik (Scientia Danica. Humanistica 4, 2016)
"The vast collections of Egyptian objects on display in Western museums attract millions of visitors every year, and they reinforce a cultural fascination for this ancient civilisation that has been a feature of European intellectual history since Roman times. This book tells the story of how these objects came to be here. ... The book presents the first in-depth analysis of this market during its 'golden age' in Egypt in the late 19th and early 20th Century. It is primarily based on the archival material of the Danish Egyptologist H. O. Lange (1863-1943) who, during two prolonged stays in Egypt (1899/1900 and 1929/1930), bought objects on behalf of Danish museums. The travel diaries, and the accompanying photographs, are complemented by a wide range of other sources, including contemporary travel guides and various travel memoirs, which together paint an extraordinarily detailed picture of the extensive antiquities trade."